Optimization of phase change materials as backfill materials for underground cable / Muhammad Naziem Mohd Salehen, Nazirah Mohd Apandi and Tengku Nur Alyani Tengku Nasharuddin - Mohd Salehen, Muhammad Naziem; Mohd Apandi, Nazirah; Tengku Nasharuddin, Tengku Nur Alyani (Penerbit UiTM (UiTM Press), 2024)
In recent years, the application of phase change materials (PCMs) has gained increasing interest due to their potential for energy conservation and thermal comfort in buildings. However, due to a limitation of study on backfilling PCM, only a few studies have examined the effects of backfill materials on ground heat exchanger characteristics. Hence, this research was conducted to identify if paraffin suitable for use as thermal backfill materials, as well as the qualities and performance as thermal backfill materials. Various percentages of paraffin wax (0%, 2%, 4%, 6%, 8%, and 10%) were mixed with Ordinary Portland Cement (OPC) and 10% fly ash to prepare concrete specimens. These specimens were tested for compressive strength, thermal conductivity, heat storage, and thermal stability. The results showed that specimens with 10% paraffin wax content exhibited a 13.63 J/g heat storage capacity and a reduced thermal conductivity of 0.5769 W/m·K, compared to 4.62 J/g and 0.7812 W/m·K for specimens without paraffin. Compressive strength tests revealed that although the presence of paraffin wax reduced compressive strength by 10%, it still increased over time with curing, achieving 48.94 MPa after 28 days. Additionally, specimens with higher paraffin content demonstrated improved thermal stability, with SEM analysis showing reduced porosity and more homogeneous microstructure. These findings indicate that higher paraffin content significantly enhances heat storage capacity, reduces thermal conductivity, and improves thermal stability, effectively managing the thermal load of underground cables.